Assessment of soil-transmitted helminth (sth) contamination in an elementary school in Talalora, Samar - Obzunar, Alessa Belle C.; Lago, Catherine B. (2024)
Soil-transmitted helminth (STH) infections caused by STH contamination in soil raise a major public health concern in communities with poor access to water and sanitation especially for elementary children. The present study aims to determine the presence of STH eggs and larvae in an elementary school in Talalora, Samar. Seventy- five soil samples and 10 dog fecal samples were collected from the playground, garden, canteen area, outside the classroom premises, and near garbage or toilets where STH was most likely present. The soil and dog fecal samples were transported to the University of the Philippines Tacloban College for laboratory processing using the modified sucrose flotation method and formalin ethyl-acetate concentration technique, respectively. Physicochemical parameters of soil such as temperature, pH, and texture were also determined. Results show the presence of Ascaris sp.. hookworm/Strongyloides, and Trichuris sp. in the samples. Hookworm/Strongyloides sp. was the only STH detected in soil samples from the canteen and outside classrooms (2.67%), while all three STH were found in dog fecal samples collected from the playground, canteen, and outside classrooms (30.00%). Hookworm/Strongyloides sp. had the highest mean density for both soil (30 epg) and dog fecal samples (6 epg), followed by Trichuris sp. (5 epg) and Ascaris sp. (2 epg). The results of the study reveal STH contamination in soil and stray dogs are reservoir hosts of STH.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.